An Analytical Framework for Assessing the Effect of Income from Non-timber Forest Products on Poverty Alleviation in Savannah Region, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
The study objective was to develop an analytical framework toassess the effect of income from non-timber forest products (NTFPs) onpoverty alleviation in the Savannah region of Sudan. The study developeda conceptual framework based on a production-to-consumption system. Aframework was developed from the analysis of three case studies selectedfrom the Savannah region of Sudan based on their economic value. Theframework considered income from NTFPs to be influenced by resourcebase, markets for the products and households’ characteristics within thepolitical environment. The effect on poverty alleviation was achieved bythe potential traded products through the creation of capital invested inother livelihood activities. The developed framework could potentially beof direct value to assess the impact of income from NTFPs on povertyalleviation in the Savannah region. It also directs decision makers anddevelopment planners to focus on those NTFPs with the highest capacityfor poverty alleviation; and to diagnose factors influencing the NTFPsfinancial returns. Research on other NTFPs from different areas withinthe Savannah region is highly recommended to facilitate comparison andgeneralization.
Keywords: Forest products; rural income; poverty alleviation; Savannah region; Sudan